The Diachrony of Ditransitives 2020
DOI: 10.1515/9783110701371-005
|View full text |Cite
|
Sign up to set email alerts
|

5. The emergence of the dative alternation in Dutch: towards the establishment of a horizontal link

Abstract: Present-day Dutch displays a productive argument structure alternation between a double object construction with bare NP Theme and Recipient object and a prepositional-dative in which the Recipient is marked by the preposition aan. The latter construction is the younger of the two: it is a post-Middle Dutch innovation, which became a well-established part of the grammar of Dutch in 17 th century language only. The present paper investigates the emergence of an embryonic dative alternation in the immediately pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…to church; Zehentner 2019, 307-319) and was gradually extended to other, non-locative contexts in analogy to such instances. This is also suggested in Colleman's (2020) analysis of recipient marking in Dutch, where he states that a PP-pattern with aan came to be used for this meaning, "progressing through a series of micro-steps" (2020, 161), in a "a gradual expansion […] to more and more 'dative ' contexts" (2020, 162). The synchronic 'gradience' of the to-PP in English (or aan-PP in Dutch) as expressing a range of relations including both 'goals', 'abstract goals', and 'recipients' (which can be modelled as distinct sub-constructions with separate meaning parts) would then be the result of gradualness in diachronic change.…”
Section: Introductionmentioning
confidence: 87%
“…to church; Zehentner 2019, 307-319) and was gradually extended to other, non-locative contexts in analogy to such instances. This is also suggested in Colleman's (2020) analysis of recipient marking in Dutch, where he states that a PP-pattern with aan came to be used for this meaning, "progressing through a series of micro-steps" (2020, 161), in a "a gradual expansion […] to more and more 'dative ' contexts" (2020, 162). The synchronic 'gradience' of the to-PP in English (or aan-PP in Dutch) as expressing a range of relations including both 'goals', 'abstract goals', and 'recipients' (which can be modelled as distinct sub-constructions with separate meaning parts) would then be the result of gradualness in diachronic change.…”
Section: Introductionmentioning
confidence: 87%
“…We will first examine the diachrony of ditransitive constructions in Latin, then we will evaluate their Romance outcomes also in comparison with English, where, starting from a similar scenario, ditransitives followed a different path of change. It will be shown that, apart from the ‘macro‐tendencies’ and the ‘macro‐changes’ which are, more or less, under the eyes of the researchers, also individual tendencies and individual changes count in order to understand how languages evolve, where ‘individual’ refers not only to single authors (Petré & Van de Velde 2018; Colleman 2020; Stein 2020) but also to single verbs, suggesting the conclusion that each form has its own history (or at least, it may have, in the specific synchronic stage analysed), and confirming, once more, that ‘the past helps us to explain the past’ (Mancini 2019: 47). However, when individual histories of individual forms finally converge on the same result, as happened in Romance, a comprehensive explanation is also needed.…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal links have been posited, for example, between alternating variants such as the two English verb-particle constructions (e.g. turn off the TV vs. turn the TV off; Cappelle 2006; see alsoColleman 2020;Zehentner 2019) and between members of constructional paradigms, such as different clause types in Dutch (verb-initial, verb-second, and verbfinal; Van de Velde 2014; see also Sommerer 2020; Diewald 2020).…”
mentioning
confidence: 99%